Implementation of Game-Based Learning Methods to Improve the Learning Activities of 10th Grade Students in Sociology Classes at Baiturahmah High School, Padang - Yenni Melia; Ahmad Hidayah; Felia Siska; Yanti Sri Wahyuni; Erningsih Erningsih; Jamiah Nurul Husna; Makmur Harun (Universitas Muhammadiyah Mataram, 2026)
This study was motivated by the low level of learning activity among tenth-grade students in Sociology classes at SMA Baiturahmah Padang. The purpose of this research was to implement a game-based learning method (Game-Based Learning) to improve students’ learning activities. The research employed a Classroom Action Research (CAR) approach following John Elliot’s model, which consists of four stages: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. The data were collected through observations of students’ learning activities and assessments based on five indicators: listening, reading, writing, discussion, and participation. The data were analyzed using descriptive qualitative and quantitative techniques, including percentage calculations and mean scores to measure the improvement of students’ learning activities in each cycle. … The study was conducted in two cycles. The results showed a significant improvement in every aspect of students’ learning activities. Listening activities, which were initially at a moderate level, showed a notable increase in the second cycle. Reading skills also improved substantially following the implementation of the game-based learning method. Writing activities exhibited the greatest improvement among all indicators, indicating that this method effectively motivated students to take more active notes and write during the lessons. Class discussions became more dynamic, showing a marked increase in participation among students who were previously passive. Similarly, overall classroom participation increased considerably in the second cycle. In general, students’ learning activities improved from a moderate to a high level after the application of the Game-Based Learning method. In conclusion, the implementation of the Game-Based Learning method in Sociology learning proved effective in enhancing the learning activity of tenth-grade students at SMA Baiturahmah Padang, as it successfully fostered enthusiasm and motivation to learn students who were once mostly silent began to actively speak and participate in the learning process.